Characterization of Nepalese rice (Oryza sativa L.) landraces for qualitative traits - Kharel, Raju; Subedi, Sujan; Ghimire, Diwas; Shrestha, Suraj (Journal of Agriculture and Natural Resources, 2022)
The characterization of rice (Oryza sativa L.) landraces enables to identify phenotypically unique variables which certainly aid in rice breeding program. So, an experiment was conducted in alpha designed to characterize 188 rice landraces from NAGRC (National Agriculture Genetic Resources center) Nepal for their qualitative agromorphologies in research farm of Agriculture and Forestry University (AFU), Rampur, Chitwan in 2020 AD. Twenty-nine qualitative variables viz; twelve leaf characters, six culm characters, four panicle character and seven grain characters were observed and 26 characters revealed diverse trait expressions for each variable in experimented 188 rice accessions. Two leaf characters namely ligule colour and flag leaf attitude for early observation and one grain character (stigma colour for early observation) showed no variation among studied rice accessions. The intensity of green colour of leaf blade, culm lodging resistance and culm habit, secondary branching of panicle, and lemma and palea colour, lemma apiculus colour and sterile lemma colour, elucidated the higher variation in studied characters. The distinction revealed in qualitative characters approves the presence of abundant phenotypic diversity in the landraces assemblage and that eventually signifies the efficient and effective utilization of landrace in rice breeding programs.